Unravelling tool edge trajectory patterns: Implications on surface roughness in end milling process / Fatiha Naziera Yusof, Mohd Fauzi Ismail and Rizal Mohamed Noor - Yusof, Fatiha Naziera; Ismail, Mohd Fauzi; Mohamed Noor, Rizal (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
This study examines the effect of end milling on surface roughness in modern manufacturing. Mathematical equations simulate and analyse the tool edge trajectory of a two-flute end mill during end milling. The results are refined using MATLAB and watershed segmentation. An aluminium alloy flat bar is end-milled using a CNC milling machine for the experimental phase. Optical 3D surface measurements provide roughness data for analysis. The study shows that higher spindle speeds produce smoother surfaces with improved surface quality. The correlation matrix analysis highlights the significance of spindle speed in shaping surface roughness, and tool trajectories are associated with softer surfaces at elevated speeds for the spindle speed ranging between 1000 to 3500 rpm. The study offers valuable insights into the complex relationship between tool edge trajectories and surface roughness.